Implementation of the Make a Match Cooperative Learning Model Assisted by Picture Cards in Classroom Science Learning - Putri Monika Syari; Sulistiyono Sulistiyono; Yadri Irwansyah (EDUJAVARE: International Journal of Educational Research, 2026)
Education plays an important role in improving the quality and integrity of individuals. Education is also a consciously designed and carried out effort to create a teaching and learning process and learning environment that allows students to actively develop their potential. This study aims to determine the mastery of science learning outcomes among fifth-grade students at SD Negeri 59 Lubuklinggau through the application of the Make a Match cooperative model using picture cards. The main problem in this study was the low student learning outcomes, with only 26.92% achieving the mastery score. The research method used was a quantitative pre-experimental approach with a one-group pretest-posttest design. The sample consisted of 26 fifth-grade students. Data were collected through objective tests and analyzed using a one-sample t-test. The results showed an increase in the average score from 58,97 (pretest) to 74,36 (posttest). The hypothesis test obtained a calculated t-value (2.202) > t-table (1.708), thus concluding that the application of the Make a Match model using picture cards significantly improved the science learning outcomes of fifth-grade students at SD Negeri 59 Lubuklinggau.